Characterization of Polysaccharides with Antioxidant and Hepatoprotective Activities from the Edible Mushroom Oudemansiella radicata - Qin Liu; Mengjuan Zhu; Xueran Geng; Hexiang Wang; Tzi Bun Ng (Molecules, 2017)
The preliminary structure, in vitro antioxidant and in vivo hepatoprotective activities of water-soluble polysaccharides (ORWP) and alkali-soluble polysaccharides (ORAP), prepared from the mushroom Oudemansiella radicata, were investigated. Both ORWP and ORAP were heteropolysaccharides with mannose, glucose and galactose being the main monosaccharide components. Regarding the antioxidant activities, ORWP and ORAP showed effective 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity, hydrogen peroxide scavenging activity and lipid peroxidation inhibitory effects, as well as moderate reducing power and Fe2+ chelating activity. For the hepatoprotective activity, administration of ORWP and ORAP prevented the increase in serum alanine aminotransferase and aspartate aminotransferase activities in a carbon tetrachloride-induced acute liver damage model, suppressed hepatic malondialdehyde formation and stimulated the activities of hepatic superoxide dismutase and glutathione peroxidase. Thus, we speculate that ORWP and ORAP may protect the liver from CCl4-induced hepatic damage via antioxidant mechanisms.